2016
DOI: 10.1021/acs.bioconjchem.6b00526
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Binding Protein Self-Aggregation Drives Agglomeration of Folic Acid Targeted Iron Oxide Nanoparticles

Abstract: Folate-conjugated nanomaterials have been widely investigated for drug and imaging-agent delivery. In this work, two folic acid (FA) conjugated iron oxide particles (IOP), a ∼40 nm diameter FA-IOP and a ∼450 nm diameter FA-IOP(FA-SeraMag), were synthesized. Both particles aggregated in the presence of serum folate-binding protein (FBP) at physiological concentration and buffer conditions. Mixing 0.01% w/w FA-conjugated iron oxide particles with FBP-induced agglomeration generated an average hydrodynamic partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The FA conjugate was used to target delivery of the synthesized nanoparticles to the tumor site. 28,29 For example, Huang et al reported FA conjugated silica-modified gold nanorods as targeted CT imaging and also radiation therapy. 30 Second, for combination chemotherapy and radio therapy the CUR was loaded on Bi 2 S 3 @BSA-FA (Bi 2 S 3 @BSA-FA-CUR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FA conjugate was used to target delivery of the synthesized nanoparticles to the tumor site. 28,29 For example, Huang et al reported FA conjugated silica-modified gold nanorods as targeted CT imaging and also radiation therapy. 30 Second, for combination chemotherapy and radio therapy the CUR was loaded on Bi 2 S 3 @BSA-FA (Bi 2 S 3 @BSA-FA-CUR).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of conjugated FA was determined by UV–vis spectrophotometry analysis and calculated to be 0.9 ± 0.31 mg FA per 100 mg Bi 2 S 3 @BSA-FA. The FA conjugate was used to target delivery of the synthesized nanoparticles to the tumor site. , For example, Huang et al reported FA conjugated silica-modified gold nanorods as targeted CT imaging and also radiation therapy …”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated non-Gaussian distributions in collagen nanomorphology with D -spacing measured from 59 to 75 nm. 1320 We found that, in general, there is very little variation in D -spacings within bundles (groups of aligned fibrils) but large variations between bundles. 18 Existing models of collagen structure cannot explain these D -spacing distributions, but a recent study documented changes in collagen structure at all levels of hierarchy, including D -spacing, as a function of disease.…”
Section: Introductionmentioning
confidence: 82%
“…The structure and function of serum FBP have been extensively detailed by ourselves 1113,51,79 and others. 8095 For the purposes of this Perspective, it is important to note that FBP is derived from membrane-bound folate receptors (FRs) and plays a critical role in the complex, multiprotein process of cellular uptake of FA and in embryonic development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation